Nilai Pendidikan Agama Islam yang Terkandung dalam Relief Makam Sunan Sendang Duwur - Nashihin, Muhammad; Zuhri, Moh. Shofi; Lidinillah, Moh. Kavin (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
This study examines the values ​​of Islamic religious education contained in the reliefs of the tomb of Sunan Sendang Duwur in Lamongan, East Java. The object of this study is the reliefs found in the site of the tomb of Sunan Sendnag Duwur located in Sendang Duwur Village, Paciran District, Lamongan Regency, East Java Province. The purpose of the study was to identify and analyze Islamic teachings represented through the symbols and ornaments found in the reliefs. This study uses a qualitative method with a descriptive-analytical approach. Data were collected through direct observation, interviews with caretakers, and literature reviews. The results of the study indicate that these reliefs contain values ​​of faith, piety, and noble morals, which are represented through geometric, flora, and fauna motifs. The discussion reveals that these ornaments have symbolic meanings that teach monotheism, the importance of morals, and the relationship between humans and nature and others. The conclusion of this study is that the reliefs of the tomb of Sunan Sendang Duwur serve as a medium for Islamic education, which conveys spiritual and moral teachings to the community.